Authenticity and brain health: a values-based perspective and cultural education approach - Stirland, Lucy E.; Ayele, Biniyam A.; Correa-Lopera, Catherine; Sturm, Virginia E. (Frontiers in Neurology, 2023)
This perspective paper discusses the concept of authenticity in relation to brain health and neurodegenerative diseases. We define authenticity as being true to oneself and consider it a social value of relevance to neuroscientists, clinicians, and caregivers. From a biological perspective, behaviors that can be interpreted as expressions of authenticity are produced by distributed brain networks. By understanding it as a dynamic process, we argue that harnessing authenticity across the lifespan can be protective by promoting resilience. We discuss the idea of authentic aging, which appreciates the complexity of human life within the world and can enhance positive views of later life. Authenticity is additionally applicable to caring for people with neurodegenerative diseases, both when understanding the behavior of people with dementia and the response of caregivers. Tailoring care to an individual’s personality and strengths may improve their brain health. Finally, we describe an interdisciplinary learning event, themed around masks, designed to engage participants in identifying authenticity in their own work. For scientists, care professionals, and caregivers, reflecting upon authenticity can aid understanding of the person with dementia and therefore improve care.